Comparative Study of Type-1 and Type-2 Fuzzy System in Decision Support System - Humaira Humaira; Yance Sonatha; Cipto Prabowo; Hidra Amnur; Rita Afyenni (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2018)
This study compares the Type-1 Fuzzy and Interval Type-2 Fuzzy in Decision Support System (DSS). Particular case studied in this paper deals with supplier selection for development of new product. DSS is developed to recommend a decision to provide assessment criteria on the supplier. All the type of membership functions and rules between these systems are equally applied. It is shown that  in Type-2 Fuzzy can manage the level of uncertainty in decision making. In general, both systems have a surface resemblance. The result shows that type-2 Fuzzy based decision making with a level of uncertainty is able to provide alternative decisions.